If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1 = -6(x + 2) Reorder the terms: -1 + y = -6(x + 2) Reorder the terms: -1 + y = -6(2 + x) -1 + y = (2 * -6 + x * -6) -1 + y = (-12 + -6x) Solving -1 + y = -12 + -6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + y = -12 + 1 + -6x Combine like terms: -1 + 1 = 0 0 + y = -12 + 1 + -6x y = -12 + 1 + -6x Combine like terms: -12 + 1 = -11 y = -11 + -6x Simplifying y = -11 + -6x
| 9a+5b=1 | | x+2x+2(2x)+2(4x)=64 | | 55+165x=1540 | | B^2+16b-15=2 | | 5y-14=4 | | 5-y+3y=3-3y+3y | | 25x^2+25x-2500=0 | | H(t)=86+13t-4.9t^2 | | X^2+20+51=0 | | Z^2+i=1 | | 0=2x^2-8x+6 | | 5x+16=-18x+38 | | A^2-12a-62=0 | | x-104=64 | | (6x-5)(4x+8)=0 | | 2.5(2x+4)=30 | | 5(3x-8)-2=-33-15x | | 2b^2=-6 | | 9x^2+16=25 | | x+18x=3 | | 5(3x-8)-2=-33-15v | | 18x^3-4x^2+10x= | | 55-55= | | 6.5x+x=74 | | -6(2+a)=48 | | 6r-60=12 | | 5a^2=-13a-6 | | 7x^2-3=67 | | 6+c=22 | | c^4-9c^2+20=0 | | 5x+2=6x+-4 | | 0=9x-y+5 |